Factors Influencing the Success Of Autism Spectrum Disorders Overcoming - Gorbachevskaya N.L; Pereverzeva D.S; Voinova V.Yu; Sorokin A. B.; Koval-Zaitsev A.A; Salimova K.R; Tyushkevich S. A.; Kobzova M. P.; Danilina K.K; Mamohina U. A.; Yurov I.Yu; Vorsanova S.G; et al. (Moscow State University of Psychology and Education, 2016)
No more than 10-20% of children with autism, as becoming adults can adapt to a relatively independent life. Despite many publications dedicated to autism, relatively little work has examined the output characteristics and pathomorphosis of psychic and cognitive disorders in people with autism spectrum disorders (ASD). Only few longitudinal studies allow us to represent what happens in later life with people who have ASD. For conducting effective correctional interventions overcomingwith children with ASD there is need to identify predictors of successful overcome of disorders. The basis for the study, conducted by a team of psychologists and neuroscientists, was the assumption that the information about the features of violations of basic neurobiological mechanisms in people with autism spectrum disorders should determine the tactics of assistance. Genetic, neurophysiological and psychological factors, causing more successful overcoming of these disorders in children are revealed.